Host–Pathogen Interactions of Chlamydia trachomatis in Porcine Oviduct Epithelial Cells - Amanda F. Amaral; Bryan E. McQueen; Kimberly Bellingham-Johnstun; Taylor B. Poston; Toni Darville; Uma M. Nagarajan; Caroline Laplante; Tobias Käser (Pathogens, 2021)
Chlamydia trachomatis (Ct) causes the most prevalent bacterial sexually transmitted disease leading to ectopic pregnancy and infertility. Swine not only have many similarities to humans, but they are also susceptible to Ct. Despite these benefits and the ease of access to primary tissue from this food animal, in vitro research in swine has been underutilized. This study will provide basic understanding of the Ct host–pathogen interactions in porcine oviduct epithelial cells (pOECs)—the counterparts of human Fallopian tube epithelial cells. Using NanoString technology, flow cytometry, and confocal and transmission-electron microscopy, we studied the Ct developmental cycle in pOECs, the cellular immune response, and the expression and location of the tight junction protein claudin-4. We show that Ct productively completes its developmental cycle in pOECs and induces an immune response to Ct similar to human cells: Ct mainly induced the upregulation of interferon regulated genes and T-cell attracting chemokines. Furthermore, Ct infection induced an accumulation of claudin-4 in the Ct inclusion with a coinciding reduction of membrane-bound claudin-4. Downstream effects of the reduced membrane-bound claudin-4 expression could potentially include a reduction in tight-junction expression, impaired epithelial barrier function as well as increased susceptibility to co-infections. Thereby, this study justifies the investigation of the effect of Ct on tight junctions and the mucosal epithelial barrier function. Taken together, this study demonstrates that primary pOECs represent an excellent in vitro model for research into Ct pathogenesis, cell biology and immunity.